1993
DOI: 10.1002/j.1556-6676.1993.tb02654.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Adolescent and Adult Attachment: A Review of Current Self‐Report Measures

Abstract: Increased interest in attachment theory among counseling researchers and practitioners has led to the development of several measures of attachment‐related constructs. Following a brief overview of the theoretical foundations of attachment theory as conceptualized by Ainsworth (1989) and Bowlby (1988), the authors of this article review four self‐report measures of adolescent and adult attachment. Many considerations for the selection and use of these instruments in future counseling research and assessment ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 27 publications
2
25
0
1
Order By: Relevance
“…There is a critical need to develop reliable, valid instruments that measure the quality of individual attachment relationships (e.g., mother, father, best friend) for this age group. The Strange Situation procedure (Ainsworth et al, 1978) has been well validated for assessing attachment in infants, and a number of instruments have been developed for individuals in late adolescence and adulthood (for reviews, see Crowell et al, 1999;Lyddon, Bradford, & Nelson, 1993). Developing psychometrically sound assessment tools for late childhood and early adolescence will be necessary to advance our knowledge of the role of attachment in the parent and peer relationships for this age group.…”
Section: Future Researchmentioning
confidence: 99%
“…There is a critical need to develop reliable, valid instruments that measure the quality of individual attachment relationships (e.g., mother, father, best friend) for this age group. The Strange Situation procedure (Ainsworth et al, 1978) has been well validated for assessing attachment in infants, and a number of instruments have been developed for individuals in late adolescence and adulthood (for reviews, see Crowell et al, 1999;Lyddon, Bradford, & Nelson, 1993). Developing psychometrically sound assessment tools for late childhood and early adolescence will be necessary to advance our knowledge of the role of attachment in the parent and peer relationships for this age group.…”
Section: Future Researchmentioning
confidence: 99%
“…Lyddon, Bradford, and Nelson (1993) and Lopez and Gover (1993) have recently reviewed self-report measures used to assess attachment in adolescence and adulthood. In general, the measures used to assess attachment in the studies reviewed have adequate reliability.…”
Section: Attachment and Eating Disorders-the Evidencementioning
confidence: 99%
“…The internal consistency of the scale was high: α = .77 (T1) and α = .85 (T2). The Kandel Depression Scale is extensively employed in adolescent surveys (see review on depression measures by Compas et al 1993). Previous studies have shown sufficient internal reliability, test–retest reliability and stability over moderate periods of time (Kendall et al 1989; for Dutch data see Otten et al 2009).…”
Section: Methodsmentioning
confidence: 99%